The effect of aerobic exercise on blood sugar control in diabetes mellitus patients - Nurul Fithriati Haritsah; Dwi Kurniawati (Institute of Computer Science (IOCS), 2025)
Diabetes mellitus is a global health problem with increasing prevalence. According to data from the International Diabetes Federation (1), more than 537 million people worldwide suffer from DM. Aerobic exercise has been recommended as a non-pharmacological intervention to control blood glucose levels, but further research is needed to determine its effectiveness in various clinical contexts. Various measures are taken to prevent and control diabetic neuropathy and improve peripheral circulation through the five pillars of DM management, namely education, nutrition, physical activity, pharmacological therapy, and blood glucose monitoring. Physical activity is an important element in preventing and managing type 2 DM. Aerobic exercise is a series of deliberately selected movements that follow the rhythm of music that is also selected so as to create certain rhythmic, continuity, and duration provisions. Subjects and Method: This study used 30 subjects with a quasi-experimental method with one group pretest and posttest design with control. The total sample was 30 patients, namely 15 in the intervention group and 15 in the control group. This study was conducted on subjects aged 40-60 years in Tohudan Village, Colomadu, Karanganyar. The intervention group underwent an aerobic exercise program three times a week for 12 weeks, while the control group did not receive any intervention. Blood sugar levels were measured before and after the intervention. Results: There was a significant effect between random blood glucose levels in patients given the intervention, with a mean difference of -46,000, indicating that after being given an aerobic exercise intervention, random blood glucose could decrease by about 46 mg/dl. Conclusion: There is an effect of aerobic exercise on blood sugar control in patients with diabetes mellitus.